A pilot project to store carbon as biomass in African woodlands. Issue 2 (December 2010) - Grace, J; Ryan, CM; Williams, M; Powell, P; Goodman, L; Tipper, R
Capturing carbon by planting trees or avoiding deforestation is thought to be a cost-effective way to reduce the inexorable rise in CO2 in the atmosphere. We describe a way to motivate African farmers to plant trees and protect woodland, based on a Mozambican pilot project in the voluntary carbon market. By late 2009, 1510 farmers were enrolled. Between 2003 and 2009, the project was able to sell carbon credits totaling approximately US$1.3 million on the voluntary carbon market, corresponding to 156, 000 tCO2, at a price that averaged US$9.0 per ton. Moreover, the effect of the carbon project was to increase rural employment from 8.6 to 32%, whilst 73% of households raised commercial crops compared with 23% previously. There was also a notable development of social capital, with a measurable increase in literacy and the development of a business ethos with associated practical skills.